The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1139/cjps-2017-0254
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-based identification of genes related to resistance against Botrytis elliptica in Lilium regale

Abstract: A major production constraint of lilies is gray mold caused by the necrotrophic fungus Botrytis elliptica. The molecular basis of lily plant resistance to B. elliptica remains largely unexplored. To systematically dissect transcriptomic responses, we constructed four RNA-seq libraries from the leaves of Lilium regale, a promising Chinese wild Lilium species, after B. elliptica infection for 0, 4, 12, or 24 h. The sequence reads were assembled into 96 416 unigenes, of which 7697 were differentially expressed. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 64 publications
4
17
0
Order By: Relevance
“…The N50 length of these unigenes was 908 bp, and the average length was 575 bp. These results were comparable to what obtained in other recent studies in species of the Liliaceae family, such as Lilium regale (N50 = 920 bp, average length = 682 bp) (Cui et al, 2018). The number of unigenes and contained SSRs obtained from the present study (92,107 unigenes with 3,430 SSRs) was also close the number identified in other three Liliaceae species (L. formolong, L. longiflorum, and L. longiflorum) (average unigenes = 72,256) (Biswas et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…The N50 length of these unigenes was 908 bp, and the average length was 575 bp. These results were comparable to what obtained in other recent studies in species of the Liliaceae family, such as Lilium regale (N50 = 920 bp, average length = 682 bp) (Cui et al, 2018). The number of unigenes and contained SSRs obtained from the present study (92,107 unigenes with 3,430 SSRs) was also close the number identified in other three Liliaceae species (L. formolong, L. longiflorum, and L. longiflorum) (average unigenes = 72,256) (Biswas et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Taken together, our analysis indicates that SA and JA signaling pathways play pivotal roles in B. elliptica-Sorbonne" interaction. This supports the proposal that a large number of transcripts related to B. elliptica resistance in L. regale were involved in the JA and phenylpropanoid pathways (Cui et al, 2018a). Moreover, as reported in the interactions between other hosts and Botrytis spp.…”
Section: Role Of Hormone Signaling Pathways In B Elliptica-"sorbonne" Interactionsupporting
confidence: 89%
“…To validate the RNA-seq data, the expression of 10 defenserelated DEGs, including four DEGs involved in plant-pathogen interactions (Cui et al, 2018a) and six DEGs involved in the phenylpropanoid and flavonoid biosynthesis pathways, was analyzed by qRT-PCR. The qRT-PCR was performed using the SsoFast EvaGreen Supermix (Bio-Red, USA) on the CFX96 Real-Time PCR Detection System (Bio-Rad, USA) under the following conditions: 95 • C for 30 s, followed by 39 cycles of 95 • C for 5 s and 57 • C for 5 s, melt curve 65-95 • C, increment 0.5 • C for 5s.…”
Section: Quantitative Real-time Pcr (Qrt-pcr)mentioning
confidence: 99%
“…In recent reports, differentially expressed transcripts in L. regale response to F. oxysporum have been identified using the SSH method (Rao et al , ). Transcriptome‐wide identification has also been performed to characterize the microRNAs (Gao et al , ) and genes (Cui et al , ) with significantly changed expression in Botrytis elliptica ‐infected L. regale , and two TFs, LrWRKY4 and LrWRKY12 , have been characterized as important regulators of resistance to B. cinerea (Cui et al , ). In this study, we employed a comparative transcriptome approach to dissect the antiviral molecular mechanism in L. regale .…”
Section: Discussionmentioning
confidence: 99%